Study of Vertical Ga2O3 FinFET Short Circuit Ruggedness using Robust TCAD Simulation. (1st November 2022) - Lu, Albert; Elwailly, Adam; Zhang, Yuhao; Wong, Hiu Yung
Abstract : In this paper, the short circuit ruggedness of Gallium Oxide (Ga2 O3 ) vertical FinFET is studied using Technology Computer-Aided-Design (TCAD) simulations. Ga2 O3 is an emerging ultra-wide bandgap material and Ga2 O3 vertical FinFET can achieve the normally-off operation for high voltage applications. Ga2 O3 has a relatively low thermal conductivity and, thus, it is critical to explore the design space of Ga2 O3 vertical FinFETs to achieve an acceptable short-circuit capability for power applications. In this study, appropriate TCAD models and parameters calibrated to experimental data are used. For the first time, the breakdown voltage simulation accuracy of Ga2 O3 vertical FinFETs is studied systematically. It is found that a background carrier generation rate between 10 5 cm −3 s −1 and 10 12 cm −3 s −1 is required in simulation to obtain correct results. The calibrated and robust setup is then used to study the short circuit withstand time (SCWT) of an 800 V-rated Ga2 O3 vertical FinFET with different inter-fin architectures. It is found that, due to the high thermal resistance in Ga2 O3, to achieve an SCWT >1 μ s, low gate overdrive is needed which increases Ron, sp by 66% and that Ga2 O3 might melt before the occurrence of thermal runaway. These results provide important guidance for developing rugged Ga2 O3 power transistors.